Genetic Deficiency of Hyaluronan Synthase 2 in the Developing Limb Mesenchyme Impairs Postnatal Synovial Joint Formation - Yingcui Li; Alexander Tress; Peter Maye; Kemar Edwards; Asiona Findletar; Nathaniel A. Dyment; Yu Yamaguchi; David W. Rowe; Gengyun Le-Chan; Sunny S. K. Chan; Kevin W.-H. Lo (Biomedicines, 2025)
Hyaluronan, a key component of the extracellular matrix, plays a crucial role in joint development and maintenance. In order to determine the role of hyaluronan function in joint development and homeostasis, conditional loss-of-function experiments of Hyaluronan Synthase 2 (Has2) were carried out in mice. Has2 depletion in limb mesenchymal cells led to severely shortened limbs with appendicular joints that are deformed, decreased proteoglycan content as characterized by Safranin-O staining, and severely pitted epiphyseal ends of long bones and deformed joints as viewed by micro-CT reconstructions. The embryonic deletion of Has2 in mesoderm mesenchyme of limbs by Prx1-Cre confirmed its involvement in joint development, while in situ hybridization and hyaluronan staining confirmed Has2 expression and abundant accumulation of hyaluronan in the onset of joint formation, the joint interzone. These findings position Has2 as the main hyaluronan-making enzyme in articular cartilage and highlight its essential function in joint formation and retention of proteoglycans of the extracellular matrix of the cartilage.